Mouse Ability to Perceive Subjective Contours. (March 2016) - Okuyama-Uchimura, Fumi; Komai, Shoji
In contrast to the previously held notion that mice have a weak visual system, it is now generally accepted that mice can perceive rather complicated figures in various contexts such as in cognitive experiments and in social settings. Here, we show that mice could even be capable of perceiving a visual illusion—subjective contours. This illusion requires the visual system to compensate for a lack of visual information in compressed 2D images on the retina. In this experiment, we trained mice to respond appropriately to a rectangle-shaped rewarded figure of specific orientation in a two-choice visual discrimination task with a touchscreen monitor. In Transfer Test 1, mice could discriminate illusory rectangle-shaped figures significantly as compared with a figure, which did not induce illusory figures. In Transfer Test 2, the choice rate of targets decreased with imperfect illusory figures, which produced weak perception of rotated or deficient inducers. Moreover, in Transfer Test 3, mice could not discriminate the low-resolution illusory figure, which also induced weak perception. These results demonstrated the possibility that mice might be useful for investigating fundamental properties of the neural visual system.